Embedding Qur’anic Values into Student-Centered Learning: A Framework for Character Education in Contemporary Classrooms - Eva Syafaah Hasanah (International Journal of Educational Narratives, 2025)
Background. Contemporary education often emphasizes cognitive achievement and 21st-century skills, while character formation and spiritual values receive limited attention, particularly within Muslim educational contexts. This imbalance highlights the need for pedagogical frameworks that integrate academic learning with moral and spiritual development rooted in Islamic values. Purpose. This research aimed to formulate and examine a character education framework that internalizes Qur’anic values within student-centered learning practices in modern classrooms. Method. The study employed a qualitative approach through literature review and conceptual analysis. Data sources included curriculum documents, theoretical studies on character education, principles of student-centered learning, and Qur’anic verses emphasizing values such as honesty, responsibility, cooperation, empathy, and critical thinking. Results. The findings suggest that Qur’anic values can be effectively internalized through active learning strategies, including reflective discussions, project-based learning, contextual problem-solving, and authentic assessment. These strategies promote active student engagement, independence, and the practical application of character values in daily life. Conclusion. The study concludes that integrating Qur’anic values into student-centered learning offers a relevant and sustainable framework for holistic character education. This approach not only enhances academic participation but also strengthens moral and spiritual development, making it a contextual pedagogical model for modern classrooms.